Literature review on ability of agricultural crop residues and agro-industrial waste for treatment of wastewater - Nur Hidayat; Sri Suhartini; Tutut Arinda; Elviliana Elviliana; Lynsey Melville (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Agricultural crop residues (ACR) and agro-industrial waste (AIW) are abundant in Indonesia and primarily used as substitutes for cattle feed or to be naturally decomposed in the nearby environment. This review attempts to examine the potential valorisation of ACR and AIW into biosorbent. This paper also provides the challenges and opportunities in applying wastewater biosorption treatment in Indonesia.Method A literature review from available literature was carried out to reveal and explore the ability and prospective application of ACR and AIW   for treatment of wastewaterResults The reviews show that ACR and AIW can be used for wastewater treatment in different forms including: filter media, activated carbon, biosorbent and biochar. Activated carbon has demonstrated its high ability and efficiency in removing organic pollutants in wastewater. This is due to its large porosity, internal surface area, and mechanical strength. ACR and AIW in wastewater biosorption can be applied in any small-scale agro-industries because of their simplicity procedures, technology, and low cost. Various options of wastewater technologies have also been investigated in recent years. Yet, various issues have been aroused surrounding this technology, including the biosorptive capacity, the performance-effectiveness, the design, and the high operation costs.Conclusion The study found that problems of a high cost of carbonation and activation process, the needs of regeneration treatment, and the up-scaling or commercialization might hinder the sustainable valorisation of ACR and AIW.